Effects of forest types on soil carbon content in aggregate faction under climate transition zone - Dong, Xiongde; Zhao, Kunpeng; Wang, Jian; Gui, Haoran; Xiao, Yutong; Chen, Zhijie; Miao, Yuan; Han, Shijie (Frontiers in Environmental Science, 2023)
Variations in soil aggregates and soil organic carbon (SOC) in response to land-use change are important to understanding the carbon cycle in forest ecosystems. However, few studies investigated the effect of forest type on aggregate stability, SOC content, and particulate organic carbon (POC) content. Therefore, we collected soil and fine root samples in two natural forests (Pinus massoniana and Quercus variabilis) and a planted forest (Cunninghamia lanceolata) in a warm temperate-subtropical climate transition zone to analyze the effect of forest type on aggregate stability, SOC content, and POC content. The results showed that the mean weight diameter (MWD) of the soil aggregates was significantly higher in Quercus variabilis and Pinus massoniana forests (62% and 21%, respectively) than in the Cunninghamia lanceolata forest due to higher mycelial length density, mycelial infection rate, and glomalin content. Similarly, the SOC and POC contents were significantly higher in Quercus variabilis and Pinus massoniana forests than in the Cunninghamia lanceolata forest (p < 0.05). The dominant size fraction of aggregate were highly correlated with the carbon fraction content. The SOC and POC contents and fungal traits (mycelial length density, mycelial infection rate, and glomalin content) were significantly positively correlated with the MWD. These results indicated that natural forests had higher aggregate stability than planted forests due to a higher SOC content and more favorable fungal traits in the warm temperate-subtropical climate transition zone